INTRADIPLOIC EPIDERMOID CYST OF THE SKULL - Khalid, Shah; Shahbaz Ali Khan; Ahsan Aurangzeb; Gul Muhammad; Ehtesham Ahmad Khan Afridi; Deen Muhammad (Journal of Ayub Medical College Abbottabad, 2021)
Intradiploic epidermoid cyst is an uncommon, benign, slow growing neoplasm that occurs between two tables of cranial bones and constitute 0.4% of all cranial epidermoid. It usually occurs due to the entrapped ectodermal embyronal remnants within the skull bones or rarely secondary to trauma. Pre-operative diagnosis on the basis of radiologic investigations is difficult. Complete surgically excision is usually required in order to prevent complications like super infection, intracranial rupture with pneumocephalus and rarely malignant degeneration. We are presenting a case of incompletely resected and chronically infected intradiploic epidermoid cyst of right parietal bone operated inadvertently by a general surgeon elsewhere without doing any radiological investigations.